Internalisasi Nilai-Nilai Nasionalisme dalam Pembelajaran Pendidikan Aswaja dan ke-NU-an di Madrasah Aliyah Nasy’atul Muta’allimin - Amrullah Amrullah; Abd Hadi (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The background of this research is the attitude of a student who received Aswaja dan NU-ness education who has a nationalist attitude. The purpose of this research is to analyze the extent to which the Aswaja dan NU-ness Education lessons in which there is knowledge about nationalism can become nationalist students. This study used a qualitative approach with descriptive types and data collection techniques used, observation, interviews, and documentation. The results of this study stated that in the lesson there was material about mabadi khaira ummah, ukhuwah wathaniyah, and Nahdlatul Ulama in the nation s struggle. The nationalist attitude of students obeys teachers, school rules, sings subbanul wathan songs, attends ceremonies every Monday and santri day.